Metodologias analíticas para determinação de plumbagina em amostras de folhas e conteúdo ruminal para o diagnóstico das intoxicações por Plumbago scandens - Carlos José Rocha Teixeira (2023)
Plumbago scandens is a plant belonging to the Plumbaginaceae family, occurring in all regions of Brazil. It has been described as toxic to cattle and goats. Intoxication is characterized by caustic lesions in the upper digestive tract. P. scandens contains a naphthoquinone named plumbagin, which presents high cytotoxic activity. The objective of this work was to develop analytical methodologies for determining the levels of plumbagin in samples of leaves, steams, and rumen content, to be used as an auxiliary chemical marker in the laboratory diagnosis of intoxication. A methodology was developed using thin layer chromatography (TLC) and another using high performance liquid chromatography (HPLC). The presence of U. brizantha, M. maximum, corn silage and ruminal content did not interfere with plumbagin in any of the two methodologies. The TLC methodology generates qualitative results but is simple to implement and has a low cost. The HPLC methodology developed in this study showed excellent precision and sensitivity, where limit of detection was 0.01 μg/mL and limit of quantification was 0.05 μg/mL. Leaf and steam samples of P. scandens evaluated showed high levels of plumbagin (0.261±0.087% and 0.327±0.055%, respectively), while leaves of Plumbago auriculata (a widely used ornamental plant) did not show detectable levels of the toxin and some steam samples showed low levels (up to 0.000114%). Thus, these methodologies can be used to confirm or rule out the consumption of P. scandens in cases of animals suspected of poisoning.